2017
DOI: 10.1103/physrevlett.118.103402
|View full text |Cite
|
Sign up to set email alerts
|

Size-Resolved Photoelectron Anisotropy of Gas Phase Water Clusters and Predictions for Liquid Water

Abstract: We report the first measurement of size-resolved photoelectron angular distributions for the valence orbitals of water clusters with up to 20 molecules. A systematic decrease of the photoelectron anisotropy is found for clusters with up to 5-6 molecules, and most remarkably, convergence of the anisotropy for larger clusters. We suggest the latter to be the result of a local short-range scattering potential that is fully described by a unit of 5-6 molecules. The cluster data and a detailed electron scattering m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(79 citation statements)
references
References 49 publications
6
72
1
Order By: Relevance
“…Comparison of anisotropy parameters determined in this work and those obtained by Hartweg et al 43 for (a) 1 b 1 , (b) 3 a 1 , and (c) 1 b 2 bands of water. Experimental values for H 2 O monomer and (H 2 O) n clusters and predicted values for liquid water were taken from Ref.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…Comparison of anisotropy parameters determined in this work and those obtained by Hartweg et al 43 for (a) 1 b 1 , (b) 3 a 1 , and (c) 1 b 2 bands of water. Experimental values for H 2 O monomer and (H 2 O) n clusters and predicted values for liquid water were taken from Ref.…”
Section: Resultsmentioning
confidence: 52%
“…Hergenhahn and coworkers have measured photoemission anisotropy for neutral water clusters with the aggregation numbers ( n ) of 50–80 and attributed the diminished photoemission anisotropy to elastic scattering in the cluster 42 . Nahon, Signorell, and their coworkers have employed a coincidence imaging spectrometer at SOLEIL to measure photoemission anisotropy as a function of electron kinetic energy for neutral water clusters up to n  = 20 43 . Their results are reproduced in Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…These species should be observable spectroscopically, since recently Xie et al, using VUV photoionization in combination with IR spectroscopy, observed hemi-bonded structures in H2S clusters 106 and for (CH3SH)2 + bonded with H2O, (CH3)2CO, CH3SH and NH3. 107 Coincidence spectroscopy where mass selected photoelectron spectra can be obtained could also be applied to these PAH water clusters, as recently demonstrated for pure PAH 108 and water clusters 109 at the French synchrotron SOLEIL.…”
Section: Solvation and Reactivity In Ionized Naphthalene-water Clustersmentioning
confidence: 93%